Prophylactic Statin Therapy for the Prevention of Anthracycline-Induced Cardiotoxicity in Patients with Breast Cancer: A Systematic Review and Meta-Analysis of Randomized Controlled Trials and Cohort Studies - Nadia Karimah Amalia; Yenny Dian Andayani; Mediarty; Norman Djamaludin (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background. Anthracycline-based chemotherapy remains a cornerstone of curative-intent breast-cancer treatment but carries a dose-dependent risk of cancer therapy-related cardiac dysfunction (CTRCD). Statins exert pleiotropic anti-inflammatory, antioxidative, and endothelial-stabilizing effects that may attenuate myocardial injury; however, prior meta-analyses pooled breast-cancer and lymphoma populations, obscuring breast-cancer-specific signals. Methods. A systematic review and random-effects meta-analysis was conducted per PRISMA 2020. PubMed, Cochrane, Scopus, and Web of Science were searched for randomized controlled trials (RCTs) and propensity-matched cohort studies enrolling adult breast-cancer patients receiving anthracycline-based chemotherapy with or without trastuzumab. Co-primary outcomes were CTRCD incidence and standardized change in left-ventricular ejection fraction (LVEF, Hedges' g). Risk of bias was assessed using RoB 2.0 and ROBINS-I. Sensitivity analyses included leave-one-out exclusion and restriction to breast-cancer-only RCTs. Results. Ten studies (1,239 patients; six RCTs, four cohort studies) were included. The pooled risk ratio for CTRCD was 0.49 (95% CI 0.28–0.85; p = 0.011; I² = 0%). The pooled standardized mean difference for LVEF change was 0.38 (95% CI −0.06 to 0.81; I² = 81%), corresponding to approximately +2.1 LVEF percentage points. Sensitivity analyses restricted to breast-cancer-only RCTs strengthened the CTRCD effect (RR 0.36, 95% CI 0.16–0.82). HER2-positive subgroup analyses yielded a pooled RR of 0.28 (95% CI 0.10–0.80). Conclusion. Prophylactic statin therapy is associated with a clinically meaningful and statistically significant reduction in CTRCD in breast-cancer patients receiving anthracyclines. The protective effect is particularly pronounced in HER2-positive patients. A cautious, risk-stratified use of statins as a cardioprotective adjunct is supported pending adequately powered, breast-cancer-specific randomized trials.